2018
DOI: 10.24198/jiita.v1i2.14573
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Technical Requirement for Improving Quality of Local Online Food Delivery Service in Yogyakarta

Abstract: Increased internet usage and fast-paced consumer's demands have created business opportunities, including online food delivery services. However, competition with similar national-scale businesses allegedly contributed to the decline in the number of XYZ company orders, one of the food-delivery service providers in Yogyakarta. Therefore, this study aimed to identify the need's attributes of the daring food delivery service consumers, to find out the servicequality satisfaction level, and to determine the techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 0 publications
2
32
1
Order By: Relevance
“…This result confirms previous studies related to continuance adoption of mobile technologies and services ( Dlodlo, 2014 ; Gao et al, 2015 ; Yuan et al, 2016 ; Cao and Niu, 2019 ; Marinković et al, 2020 ). Furthermore, it has reconfirmed that satisfaction is an important determinant for users' re-purchase intentions in an FDA service context ( Elvandari et al, 2018 ). Therefore, monitoring and improving users' satisfaction by providing a high quality of service to meet customers' requirements are essential and appropriate approaches for FDAs providers to retain customers during the COVID-19 pandemic, as well as sustainably maintaining future development of FDAs by satisfying customers' technological and mental expectations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result confirms previous studies related to continuance adoption of mobile technologies and services ( Dlodlo, 2014 ; Gao et al, 2015 ; Yuan et al, 2016 ; Cao and Niu, 2019 ; Marinković et al, 2020 ). Furthermore, it has reconfirmed that satisfaction is an important determinant for users' re-purchase intentions in an FDA service context ( Elvandari et al, 2018 ). Therefore, monitoring and improving users' satisfaction by providing a high quality of service to meet customers' requirements are essential and appropriate approaches for FDAs providers to retain customers during the COVID-19 pandemic, as well as sustainably maintaining future development of FDAs by satisfying customers' technological and mental expectations.…”
Section: Discussionmentioning
confidence: 99%
“… He et al (2018) illustrated that satisfaction is associated with food quality and service efficiency, which significantly affects online food delivery service adoption. Meanwhile, Elvandari et al (2018) found that order conformity, quality of delivery, food quality and costs are the most significant attributes affecting the intention of using online food delivery services. Furthermore, Ray et al (2019) implemented the uses and gratifications theory and validated that customer experience, ease-of-use and technological characteristic had significant impacts on behavioural intention to use FDAs.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Riana et al [40] and Teo et al [41] also touched on the importance of safety and promoting good hygiene from the technological adoption of using FDAs instead of physically visiting restaurants. Study of Elvandari et al [29] observed the technical requirements for improving the quality of local online food delivery services. The findings of the research indicated that perceived technology-task fit, conditions of received order, friendliness, and politeness were technical requirements for improving the quality of local online food delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Food delivery services through online apps have become a global trend, with China leading the way in the market share. The growth of the food delivery services to new markets is based on the cultivation of consumer eating habits [28] and evolving fashion trends [29]. In Thailand, for instance, the food delivery services Food Panda, Grab, Lineman, Gojeck, Lalamove, etc., have penetrated the market by offering large discounts and free delivery [30].…”
Section: Food Delivery Apps (Fdas)mentioning
confidence: 99%